(untitled) (Research, Society and Development, 2020)
The user’s degree of perception and satisfaction of an educational application is a latent construct which, in spite of being clearly real and relevant, is not directly measurable, requiring a method that establishes a metric. Among the methods available in the literature, the Exploratory Factor Analysis (EFA) stands out, in which among its purposes, the possibility of dividing a questionnaire into factors and identifying the most representative issues of the instrument used is emphasized. This article aims to extract and understand relevant factors that characterize accounting students of a Brazilian public university, regarding perception and satisfaction of the use of the Edpuzzle application. Among the results, it was found that the median of the majority of the items responded by the students, presented high levels ​​regarding the degree of satisfaction and perception. With regard to the assumptions for carrying out EFA, they were satisfactory. Finally, it was noted that items related to the perception of learning, the benefits and resources that the Edpuzzle tool provided to students, as well as the level of student satisfaction with the use of the tool, presented relevant rotated factor loads, promoting a better and concise interpretation of the latent trait.